Website Design Build Ritual Café - Mohammad Dion Hartantyo (Jurnal Sistem Informasi, 2006)
Business in the restaurant or cafe is growing, one of which is the Ritual Cafe. Likewise with internet technology, the number and range more widely. Then look at the situation, it is necessary for the Ritual Cafe to make the internet media as a means of information dissemination and promotion. To achieve this, it needs to be designed and built the website contains an information about the Ritual Cafe. Whether it's the concept, menu, price, and so on. Website design and manufacture Ritual Cafe is expected to be able to introduce the Ritual Cafe, more broadly, and can also increase the number of customers.